Wave Front Sets with respect to the Iterates of an Operator with Constant Coefficients - C. Boiti; D. Jornet; J. Juan-Huguet (Abstract and Applied Analysis)
We introduce the wave front set WF*P(u) with respect to the iterates of a hypoelliptic linear partial differential operator with constant coefficients of a classical distribution u∈𝒟′(Ω) in an open set Ω in the setting of ultradifferentiable classes of Braun, Meise, and Taylor. We state a version of the microlocal regularity theorem of Hörmander for this new type of wave front set and give some examples and applications of the former result.